Postactivation potentiation on repeated-sprint ability in elite handball players - Okuno, N. M.; Tricoli, V.; Silva, S. B. C.; Bertuzzi, R.; Moreira, A.; Kiss, M. A. P. D. M. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to analyze the changes on repeated-sprint ability (RSA) performance after heavy load exercise in elite handball players. Twelve subjects were submitted to the following experimental sessions: (a) 1-repetition maximum (1RM) test on the half squat exercise, (b) RSA test (control condition), and (c) RSA with a conditioning activity on the same exercise as 1RM test (experimental condition). The conditioning activity comprised 1 set of 5 × 50% 1RM, 1 set of 3 × 70% 1RM, and 5 sets of 1 × 90% 1RM. A significant improvement in the best sprint time (RSAbest) and mean sprint time (RSAmean) was observed with the conditioning activity (RSAbest = 5.74 ± 0.16 seconds; RSAmean = 5.99 ± 0.19 seconds) when compared with the situation without the conditioning activity (RSAbest = 5.82 ± 0.15 seconds; RSAmean = 6.06 ± 0.18 seconds; p < 0.01) with a moderate (Cohen's d = -0.54) and small effect (Cohen's d = -0.41) to RSAbest and RSAmean, respectively. Therefore, the findings of this study demonstrated that prior heavy load exercise can be used to improve the RSA performance, however, with a small to moderate magnitude of change.